Families who have a child with a disability: a literature review of quality of life issues from a Chinese perspective. Issue 2 (27th May 2022) - Ling, Guo; Potměšilová, Petra; Potměšil, Milon
ABSTRACT: The family is described as a complex system of relationships and functions of individual members. If a child with a disability is present in the family, this is an important characteristic of the family that affects the functioning of the family system. At an early age, children with disabilities are dependent on a certain level of family support that is proportional to the type and extent of their disability. The level of support subsequently affects the quality of life of the family. The literature study aimed to characterize and analyze available research on the quality of life in families with a disabled child in China. The search for relevant resources for this study was carried out in China's National Knowledge Infrastructure (CNKI), Wanfang Data, and VIP databases. The search strategy was based on the following construct: (a) the quality of life of the family; (b) AND parent OR carer OR mother OR father; (c) AND disab * OR disability OR special needs; (d) AND AB = children OR child OR student OR infant. This review consolidates the empirical research to date on families' quality of life and outlines areas of research for further exploration.